The Effect of Company Characteristics of Stock Return In Industrial Sector Manufacturing Company Basic and Chemicals Listed In The Stock Exchange Indonesia Period 2013-2017 - Eka Yulianto; iman sofian suriawinata; Rimi Gusliana Mais (Indonesian Journal of Business, Accounting and Management (IJBAM), 2018)
Abstract—This study aims to determine the effect of characteristics companies against stock returns in industrial sector manufacturing companies and chemicals listed on the Indonesia Stock Exchange in the period 2013-2017. This study uses a sample of manufacturing sector companies Basic and hemical industries as many as 22 companies listed on the Stock Exchange Indonesia with a period of five years, namely 2013-2017 and the number 110 observation. This study uses secondary data with techniques data collection using the documentation method from the official website of the Exchange Indonesian and stock effects and analyzed using Eviews Software version 10. Based on the results of research that has been done to analyze Leverage has a negative but significant effect on Stock Return this indicates a negative DER impact on increasing interest costs tax saving with companies utilizing interest costs arising from its debt to minimize the tax burden which increases financial distress caused by one of them is the increasing interest on loans high so that it will hurt the economy and increase the value of inflation. Profitability has a significant positive effect on Stock Return . Profitability goes up, so dividend expection rises resulting in stock prices going up anyway. This will encourage an increase in share prices ultimately will increase the Return stocks. Total Assets Turn Over has negative but insignificant effect on Stock Return means an increase in sales is not followed by an adequate profitability so found a negative relationship but not significant